Rechargeable Zn/PEDOT Battery with an Imidazolium‐Based Ionic Liquid as the Electrolyte. Issue 12 (8th September 2015) - Simons, Tristan J.; Salsamendi, Maitane; Howlett, Patrick C.; Forsyth, Maria; MacFarlane, Douglas R.; Pozo‐Gonzalo, Cristina
Abstract: A non‐aqueous secondary battery has been constructed by using Zn metal as the anode and chemically synthesised PEDOT as the cathode, with a 1‐ethyl‐3‐methylimidazolium dicyanamide ionic liquid as the electrolyte, which avoids dendritic growth processes on the Zn surface upon charge/discharge cycling. The novel Zn/PEDOT rechargeable cell shows high efficiency and cycling ability, performing over 320 cycles with no indication of short circuit. Both the Zn and PEDOT surfaces showed minimal signs of degradation, suggesting that a Zn/PEDOT electrochemical device would be capable of extended cycle life under numerous charge/discharge cycles. Abstract : IL be back : The performance of a novel Zn/PEDOT rechargeable battery is reported in the presence of an imidazolium‐based ionic liquid electrolyte ([C2 mim][dca]). The stability of this material is evaluated over a number of cycles and the effect of the charge/discharge rate on the cathode coulombic efficiency is studied.